Tigecycline: A Review of Properties, Applications, and Analytical Methods - da Silva, Lucelia Magalhaes [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Lippincott Williams & Wilkins, 2010)
Tigecycline is a new glycylcycline with an expanded broad-spectrum antibiotic, including inhibition of Gram-positive, Gram-negative, atypical, anaerobic, and antibiotic-resistant organisms. Trials have demonstrated that tigecycline is noninferior to the comparators for the treatment of complicated skin and skin structure infections as well as complicated intra-abdominal infections. Tigecycline is only available as an intravenous preparation and analytical methods to its quantitation in pharmaceutical products has not been published to date. This review examined tigecycline characteristics, the spectrum and mechanism of action, pharmacokinetics, applications, and, mainly, the instrumental conditions of published chromatographic methods used to measure tigecycline, its metabolites, and some analogs in clinical and biologic research.
Keywords: glycylcycline; tigecycline; analytical methods; broad-spectrum antibiotic